O MARKETING PESSOAL NO SETOR VAREJISTA: UM ESTUDO COM GESTORES NO MUNICÍPIO DE SANTA ROSA - Wagner, Wander G.; Graef, Nelinho D.; Zamberlan, Luciano; Oliveira, Charlene; Martini, Rodrigo N.; Martinelli, Marlen; Sparemberger, Ariosto; Büttenbender, Pedro L. (Salão do Conhecimento, 2013)
Resumo